Prevalence and Associated Factors of Depression among Diabetes Patients in Selected Hospital at Pokhara, Kaski - Gautam, Srijana; Shrestha, Nisha (International Journal of Social Sciences and Management, 2021)
Although in recent decades depression and diabetes patients are increasing the numbers and proportions worldwide. Eighty percent of individuals with Type 2 diabetes mellitus (T2DM) dwell in low- and middle-income countries. The real crisis of depression and diabetes, where it exists, is the personal crisis of day-by day. The objectives of this study is to determine the prevalence and associates factors of depression among diabetic patients in selected hospital in Nepal. A cross sectional study was conducted at tertiary center of Pokhara, Kaski .Study participants identified with type 2 diabetes mellitus (n=330) .Blood pressure, anthropometrics (height, weight and hip circumference) and glycated hemoglobin (HbA1c) were collected, a semi-structured interview was utilized to obtain information on socio-demographic and Beck Depression Inventory (BDI) was used as a tool to assess depressive symptoms among patients with type 2 diabetes mellitus .Logistic regression was used to investigate the associate factors of depression with diabetes patients. Majority (68.2%) of the respondents had no depression with diabetes, 16.7% of respondents having moderate, 12.4% having mild and few (2.7%) had severe depression with diabetes. Depression was significantly associated with Marital status (p=0.014), Educational status (0.016), Occupational status (p=0.003) and Drinking alcohol(p=0.020). The prevalence of depression with Diabetes in this study was 31.8%. Int. J. Soc. Sc. Manage. Vol. 8, Issue-3: 426-432